The Rice Eukaryotic Translation Initiation Factor 3 Subunit e (OseIF3e) Influences Organ Size and Pollen Maturation - Wang, Wenyi; Xu, Mengyun; Liu, Xuejiao; Tu, Jumin (Frontiers in Plant Science, 2016)
Eukaryotic translation initiation factor 3 (eIF3) is a large protein complex that participates in most translation initiation processes. While eIF3 has been well characterized, less is known about the roles of individual eIF3 subunits, particularly in plants. Here, we identified and characterized OseIF3e in rice (Oryza sativa L.). OseIF3e was constitutively expressed in various tissues, but most strongly in vigorously growing organs. Transgenic OseIF3e-silenced rice plants showed inhibited growth in seedling and vegetative stages. Repression of OseIF3e led to defects in pollen maturation but did not affect pollen mitosis. In rice, eIF3e interacted with eIF3 subunits b, d, e, f, h, and k, and with eIF6, forming homo- and heterodimers to initiate translation. Furthermore, OseIF3e was shown by yeast two-hybrid assay to specifically bind to interactors of cyclin-dependent kinases 1, 5, and 6. This interaction was mediated by the sequence of amino acid residues at positions 118–138, which included a conserved motif (IGPEQIETLYQFAKF). These results suggested although OseIF3e is not a “functional core” subunit of eIF3, it still plays crucial roles in rice growth and development, in combination with other factors. We proposed a pathway by which OseIF3e influence organ size and pollen maturation in rice, providing an opportunity to optimize plant architecture for crop breeding.